The role of cardiac rehabilitation in patients with atrial fibrillation and heart failure - Andreea Ganea; Gabriel Guşetu; Bogdan Caloian; Dumitru Zdrenghea; Dana Pop (Balneo and PRM Research Journal, 2024)
This review investigates the role and effectiveness of cardiac rehabilitation in individuals di-agnosed with atrial fibrillation and heart failure. A comprehensive analysis of existing litera-ture, clinical trials, and observational studies was conducted to assess the outcomes associated with cardiac rehabilitation interventions in this specific patient population. The complex and bidirectional relationship between atrial fibrillation and heart failure underscores the im-portance of a patient-centered approach that integrates medical, lifestyle, and rehabilitative in-terventions for optimal care and outcomes. Results suggest improved functional capacity, en-hanced quality of life, and potential favorable cardiovascular outcomes. The review brings new insights to the existing literature, emphasizing the importance of personalized cardiac rehabil-itation strategies in optimizing the overall well-being of these patients.